DIFFERENTIATED INSTRUCTION IN ACCOMMODATING INDIVIDUAL DIFFERENCES OF EFL STUDENTS - Pradana Akbar Tanjung; Ashadi Ashadi (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2019)
ABSTRACTMany EFL (English as a Foreign Language) classrooms all around the globe are full of students with individual differences. Evidently, the students possess individual differences because they come from various settings with diverse backgrounds. The divergences among students might be unique in nature and they could possibly affect the English teaching and learning process. One of the clear examples is the fact that not all learning instructions provided by teachers are effective in accommodating the differences in the classroom. This situation leads to the emergence of implementing differentiated instruction, often believed to be able to give the students equal chances to learn and experience English effectively at their full potential. This library-based paper reviews several previous practices of differentiated instruction in English classrooms. Further, it attempts to examine how differentiated instruction has been implemented in various EFL contexts. It also attempts to reveal the fundamental reasons behind the success of differentiated instruction in the many English classrooms by relating theories and practices of the previous research studies focused on the topic. This paper ends with a summary of the various findings and discusses it in the light of theories and literatures in differentiated instruction with a particular interest in EFL settings.